STRATEGIC LAWSUITS AGAINST JOURNALISTS - AN UNCONVENTIONAL WAY TO ENACT CIVIL LIABILITY - Sorin-Alexandru VERNEA (Challenges of the Knowledge Society)
In the last decade, a new way of bringing journalists to civil liability has gained momentum, which is also a form of intimidation in carrying out their activity, namely SLAPP (strategic law-suit against public participation) trials. This paper analyses the essential elements necessary to qualify a trial filed against a journalist as a slaptrial, starting from two relevant European acts: the Proposal for a directive of the European Parliament and of the Council on protecting persons who engage in public participation from manifestly unfounded or abusive court proceedings („strategic lawsuits against public participation”) and the Commission Recommendation (EU) 2022/758 on protecting journalists and human rights defenders who engage in public participation from manifestly unfounded or abusive court proceedings ('strategic lawsuits against public participation'). As it has been pointed out, there are at least two essential elements that qualify a law-suit as a SLAPP-trial and identifying them is only a prerequisite of the correct qualification, that may also imply subjective elements as bad faith, or abuse of law.